Intellectual capital and corporate profitability: Zooming into value added intellectual coefficient - Ting, Irene Wei Kiong; Kweh, Qian Long; Asif, Jawad; Hanh, Le Thi My (Inderscience Enterprises Ltd., 2022)
This study examines how value-added intellectual coefficient (VAIC™) and the modified VAIC™ affect corporate profitability. Using a Vietnamese corporate financial dataset of 1,624 firm-year observations for the period of 2009-2018, this study finds that intellectual capital (IC), as estimated by VAIC™ and modified VAIC™, has positive impacts on corporate profitability. However, the positive association between IC and profitability is clearer in the scatterplot involving the modified VAIC™. Although VAIC™ and modified VAIC™ consistently suggest positive impacts of IC on corporate profitability, the components of the two show different outcomes. This study stimulates the need to further examine not only VAIC™ but also other IC measurement models to help practitioners better estimate their IC for the best possible corporate profitability.